Pengaruh kompetensi aparatur desa, sistem pengendalian internal, pemanfaatan teknologi informasi dan partisipasi masyarakat terhadap akuntabilitas pengelolaan dana desa - Pahlawan, Enggar Wahyuning; Wijayanti, Anita; Suhendro, Suhendro (Indonesia Accounting Journal, 2020)
Accountability of village funds management is the responsibility of the village officers. Village officers should have good competency. Its can help village officer to manage village funds. Another thing in managing village funds besides of good internal controlling system is the use of information technology and public participation. This study aims to know the effect of competency of village officers, internal controlling system, use of information technology, and public participation on the accountability of village fund management. This study uses a quantitative approach for hypothesis testing. The instrument of this study is in the form of questionnaires and filled by respondents. The population in this study is all village officers in Sub-District of Grogol at Regency of Sukoharjo. The sampling technique of this study is purposive sampling with 40 respondents as the sample and analyzed by multiple linear regression. This study finds that the competency of village officers and public participation are significant on accountability of village funds management. Also, this study finds that internal controlling system and use of information technology are insignificant on accountability of village funds management.